Asian Values in International Dispute Settlement: Issues of Parallel Jurisdiction - Huang, HaiJing; Ong, Tze Chin (UI Scholars Hub, 2025)
Asian Values promoted significant economic growth to Asian societies in 1990s but were challenged by the 1997-1998 financial crisis. Engaging in regional trade agreements (RTAs) can enhance market access and keep regulatory cooperation, the number of RTAs has grown explosively in Asian countries. Most of these RTAs may include more far-reaching form of dispute settlement provisions distinct from or parallel to the World Trade Organization (WTO). Historical analysis is employed to examine the applicable principles of Asian Values and their influences on economic growth and dispute settlement. Additionally, the article also conducts case study analysis of several trade disputes with choice-of-forum clauses before the WTO panel within Asian countries, thereby assessing the interplay between RTAs and WTO jurisdictions. The research reveals ambiguities issues in parallel jurisdiction among dispute settlement mechanism of Asian RTAs and that of the WTO. The standstill of appointing WTO Appellate Body members and the proliferation of RTAs with Asian Values-oriented dispute settlement mechanisms have intensified these challenges. This article demonstrates the increasing popularity of alternative dispute resolution mechanisms rooted in Asian Values. It proposes integrating Asian Values into international dispute settlement to resolve parallel jurisdiction issues between RTAs and WTO, offering a more efficient solution to the complicated legal landscape in Asian region.